Finishing actions in relation with basketball offense outcome types in NBA and Euroleague - Selmanovic, A.; Milanovic, L.; Skegro, D. (Acta Kinesiologica, 2019)
The aim of this paper is to analyse the prevalence of tactical manoeuvres in finishing actions in professional European and American basketball, then to determine their association with the types of offensive outcomes and finally to determine the difference between the observed systems regarding their efficiency. By evaluating 5109 entities classified into 10 different types of finishing actions, a dominant presence of 1 on 1 realization facing the basket, pickand roll, getting open and open shot without getting open has been determined. The results of Chi-square test confirmed the significant difference in the frequency of distribution of modalities between European and American basketball, but there were no significant differences in their levels of efficiency, except in the finishing actions 1 on 1 facing the basket, which indicates a significantly more effective realization measures in the American basketball. According to the obtained results, the authors refer to specific tactical guidelines applicable to basketball practice